Виконавці організації життєвого циклу віртуальної спільноти - Трач, Ольга (Видавництво Львівської політехніки, 2016)
This paper presents community manager and the project team of performers stages and directions of the organization of the life cycle of virtual communities.
Keywords: віртуальна спільнота; життєвий цикл; менеджер; виконавець напряму; виконавець етапу